Kilka uwag o języku w polskim przekładzie „ Ulissesa" Joyce’ a (na podstawie VII epizodu) - SZCZERBOWSKI, TADEUSZ (Stylistyka, 2021)
It is commonly known that ’Ulysses’ presents a challengeis to translators (Senn 1972) and that the rhetoric episode ’Aeolus’ abounds in different language games. Some of them, such as the hypocoristic Doughy Daw (cf. its paronym Doughty Dawson), the homoioteleuton mouth south: tomb womb, the tautogram Dear Dirty Dublin, the anagram feetstoops, the metagram clamn dever, the paronomasia Rose of Castile, and the palindromes Madam, I’m Adam. And Able was I ere I saw Elba, are analyzed in translation. The author considers not only Polish, but also German, F rench, Russian and Byelorussian versions of ’Ulysses’. While Goyert’s translation is very literał, Słomczyński’s version is not literał. It is often an attempt at translating the idea of the language game rather than the language game itself, which would be utterly impossible.